Derivadas 11-19
  • 1. f(x)=2x2-1
A) 2x*2x2-1*In2
B) 2x*2(x2-1)*In2
C) f'(x)=2x*2x2-1*In2
D) 2x*4x2-1*In2
  • 2. f(x)=x3*e-3x
A) 3x2*e-3x(1-x)
B) f'(x)=3x2*e-3x(1-x)
C) 3x2*e(-3x)(1-x)
D) 3x2*In-3x(1-x)
  • 3. f(x)=x cosx + 2 tanx
A) f'(x)=-x senx + 2sec2x
B) f'(x)=-x tanx + 2sec2x
C) f'(x)=-x secx + 2sen2x
D) -x senx + 2sec2x
  • 4. f(x)=ex cosx
A) f'(x)=-ex senx + ex cosx
B) f'(x)=-ex senx + ex cosx
C) f'(x)=-ex cosx + ex senx
D) -ex senx + ex cosx
  • 5. y= aev + b/v * c/v2
A) aev - bv-2 - 2cv-3
B) y'= aev - bv-2 - 2cv-3
C) y'= vea - bv-2 - 2cv-3
D) y'= aev - bv-2 - 2cv-3
  • 6. f(x)=sen(cotg2x)
A) f'(x)=-2/sen22x * cotg(cos2x)
B) f'(x)=-2/sec22x * cos(cotg2x)
C) f'(x)=-2/sen22x * cos(cotg2x)
D) -2/sen22x * cos(cotg2x)
  • 7. f(x)= cos(in(4x2 + x))
A) f'(x)=-8x*1/4x2 +x sec(In(4x2 + x))
B) f'(x)=-8x*1/4x2 +x sen(In(4x2 + x))
C) -8x*1/4x2 +x sen(In(4x2 + x))
D) f'(x)=-8x*1/4x2 +x sen(In(4x4 + x))
  • 8. f(x)=e3x2+1
A) f'(x)=6xe3x2+1
B) f'(x)=3xe3x2+1
C) f'(x)=6xe(3x2+1)
D) 6xe3x2+1
  • 9. y= 2secx -cscx
A) y'= secx tanx + cscx ctgx
B) y'= 2senx tanx + cscx ctgx
C) y'= 2secx tanx + cscx ctgx
D) 2secx tanx + cscx ctgx
  • 10. f(x)=csc22x
A) f'(x)=-4cot2 2x csc 2x
B) -4csc2 2x cot 2x
C) f'(x)=-2csc2 2x cot 2x
D) f'(x)=-4csc2 2x cot 2x
  • 11. f(x)=tan2x
A) f'(x)=2 secx tan2x
B) f'(x)=2 tanx sec2x
C) f'(x)= tanx sec2x
D) 2 tanx sec2x
  • 12. f(x)=53x-4
A) 3*53x-4*In5
B) f'(x)=3*5(3x-4)*In5
C) f'(x)=3*53x-4*In3
D) f'(x)=3*53x-4*In5
  • 13. f(x)=x2 senx
A) f'(x)=2x cosx * 2x senx
B) x2 cosx * 2x senx
C) f'(x)=x2 senx * 2x cosx
D) f'(x)=x2 cosx * 2x senx
  • 14. f(x)=csc (x/2)
A) f'(x)= - cos(x/2)*2sen2(x/2)
B) f'(x)= - cos(x/2)/2sen2(x/2)
C) - cos(x/2)/2sen2(x/2)
D) f'(x)= - sen(x/2)/2cos2(x/2)
  • 15. y= 3ex + 4/x1/3
A) y'= 4/3x-4/3+3ex
B) y'= - 4/3x-4/3+3ex
C) - 4/3x-4/3+3ex
D) y'= - 4/3x-4/3+3ex
  • 16. f(x)=sen 5x
A) f'(x)=5cos5x
B) f'(x)=sec5x
C) f'(x)=5sen5x
D) 5cos5x
  • 17. f(x)=cotg(4x+5)
A) -4csc2(4x+5)
B) f'(x)=-4cos2(4x+5)
C) f'(x)=-4csc2(4x+5)
D) f'(x)=4csc2(4x+5)
  • 18. f(x)=secx3
A) 3x2secx3tanx3
B) f'(x)=3x2tanx3secx3
C) f'(x)=secx3tanx3
D) f'(x)=3x2secx3tanx3
Created with That Quiz — where test making and test taking are made easy for math and other subject areas.